RELATIONSHIP BETWEEN ANXIETY AND NOMOPHOBIA AMONG STUDENTS AT MUHAMMADIYAH UNIVERSITY PONTIANAK - Aprilia Putri Wardhani; Nur Kur'ani; Sri Nugroho Jati (Jurnal EMPATI, 2025)
Nomopobia is the fear of losing contact with a mobile phone, which can cause anxiety and frustration when it is not held or within reach. This study aims to examine the relationship between anxiety and nomopobia among students at Universitas Muhammadiyah Pontianak.  The research method employed was a quantitative correlational design, with the population consisting of all students at Universitas Muhammadiyah Pontianak. The sample was selected using a purposive sampling technique, involving 106 respondents. The research instruments consisted of an anxiety scale and a nomopobia scale, both of which had been tested for validity and reliability. Data analysis revealed a significant positive relationship between anxiety and nomopobia among students (r = 0.646; p < 0.05). These findings indicate that the higher the students’ anxiety levels, the higher their level of nomopobia.